Analisis Keefektifitasan Model Pembelajaran Daring Pada Masa Pandemi Covid-19 (Studi kasus: Kelas V SDN 12 OKU): Analisis Keefektifitasan Model Pembelajaran Daring Pada Masa Pandemi Covid-19 (Studi kasus: Kelas V SDN 12 OKU) - Destiarini Destiarini (INTECH, 2021)
Director General of the World Health Organization (WHO) Tedros Adhanom Ghebreyesus officially announced the Coronavirus (Covid-19) as a pandemi on Wednesday, March 11, 2020, so all world activities changed including education. The Covid-19 pandemi has forced the learning system in schools to drastically change from face-to-face meetings to online learners. Many schools that do not yet have an online learning infrastructure are forced to do online lectures. This study aims to analyze the effectiveness of online learning during the Covid-19 Pandemi. The purpose of this research is to get information about the effectiveness of the online learning process during the Covid-19 pandemi. The research uses qualitative explorative methods with inductive approaches. In this study, respondents related to 5 people consisting of 1 principal, 1 teacher, 1 teacher in the field of science, 1 parent, and 1 student. To maintain the confidentiality of the respondent's identity, the researcher named the respondents P1, P2, P3, P4, and P5. Interviews are structured with questions that are compiled and associated and developed with related literature. The result of this study is the lack of effective online learning due to the lack of facilities and infrastructure and the unpreparedness of technology education for teachers and students.